Computational study of <11¯00> symmetric tilt grain boundaries in Mg and Ti. (December 2015) - Ni, Chang; Ding, Hong; Asta, Mark; Jin, Xuejun
Graphical abstract: Abstract: The energetics of < 1 1 ¯ 0 0 > symmetric tilt grain boundaries in Magnesium and Titanium was studied based on semiempirical interatomic potential model. For both metals, similar trends of grain boundary energy as a function of tilt angle were observed. Our calculations suggested that the { 1 1 2 ¯ 3 } twin boundary is a cusp in the energy versus misorientation plot, and we demonstrated a unique crystallographic reorientation for { 1 1 2 ¯ 6 } twin structures. Structure preferences of several twin boundaries were further confirmed with density-functional-theory calculations.